PROGRAM FOR IMPLEMENTING FAMILY HOPE IN SINGKUP VILLAGE PURBARATU SUB-DISTRICT TASIKMALAYA CITY - Chandra Ardiana; Asep Nurwanda; Candra Firmanto (Faculty of Social and Political Science Universitas Galuh, 2023)
This research was motivated by observations and found a problem, namely the limited socialization of the implementing parties regarding the objectives of the Family Hope Program, the inappropriate target of the recipients of the Family Hope Program in Singkup Village because they are families with the category of being able to, and the limitations of the companion team in conducting data collection. The problem in this research is